2013
DOI: 10.3174/ajnr.a3379
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Neuroform for Treatment of Intracranial Aneurysms: A Prospective, Consecutive, French Multicentric Study

Abstract: BACKGROUND AND PURPOSE: Endovascular embolization of wide-neck intracranial aneurysms can be technically challenging, especially when the anatomy is complex. Stent reconstruction of the parent artery is commonly used to treat wide-neck and bifurcated aneurysms. The main objective of this study was to investigate the periprocedural and midterm morbidity and mortality results of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 45 publications
4
29
1
Order By: Relevance
“…The procedure-related complication rate in a study of the Neuroform SAC of unruptured aneurysms was 12.1%. 28 A metaanalysis of the SAC literature conducted by Shapiro et al 11 revealed procedure-related complications in 19% of patients. Most of these complications in the current study remained asymptomatic, and only 3.8% of the patients had a permanent morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure-related complication rate in a study of the Neuroform SAC of unruptured aneurysms was 12.1%. 28 A metaanalysis of the SAC literature conducted by Shapiro et al 11 revealed procedure-related complications in 19% of patients. Most of these complications in the current study remained asymptomatic, and only 3.8% of the patients had a permanent morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Gentric et al reported that both aspirin and clopidogrel were used more than 2 months after SAC for UICA performed using the Neuroform stent, and clopidogrel was discontinued after a mean duration of 13.6 weeks, while aspirin was discontinued after a mean duration of 32.6 weeks. However, the authors did not report on delayed ischemic events [12]. Heller et al reported on APT after treatment with the Enterprise stent; clopidogrel was discontinued after 3 months of DAPT, and then aspirin was discontinued at 6 months.…”
Section: Apt and Delayed Ischemic Event After Sacmentioning
confidence: 99%
“…Hwang et al reported rates of delayed ischemic events of 3.5% within 2 months following the switch from DAPT to SAPT [5]. Giant aneurysms, fusiform AN, incomplete occlusions, Y-stents, waffle-cone stents, stent malpositioning, Enterprise stent, and coil loop prolapse are all reported to increase the risk of delayed ischemic events after SAC [5,7,8,10,12]. Delayed in-stent restenosis is also reported to be a late complication in 2.6-14% of cases [3,7,9].…”
Section: Apt and Delayed Ischemic Event After Sacmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decades, many studies have evaluated the safety and efficacy of the technique of stent placement for intracranial aneurysms, which demonstrated a range of 3.7%-21% thromboembolic complications. 4,10,11,29 Dual antiplatelet therapy (aspirin and clopidogrel) has been used as the standard protocol to decrease the incidence of thromboembolic complications in patients with intracranial aneurysms undergoing stent treatment. However, many patients still experience thromboembolic complications after neurovascular intervention, despite being compliant with the standard antiplatelet medication protocol.…”
mentioning
confidence: 99%